Understanding and addressing Microbiologically Influenced Corrosion (MIC) - Machuca Suarez, Laura (2019)
Microbial life is everywhere. Microorganisms have been found inhabiting iced-covered lakes in Antarctica at -13°C and hydrothermal vents at the bottom of the ocean at 120°C [1]. Microorganisms have inhabited our planet for billions of years before plants and animals appeared. It was through their activities that higher forms of life could appear and thrive [2]. However, microorganisms can also be harmful and their activities can result, under certain conditions, in detrimental effects such as disease and damage to infrastructure. Industrial systems typically create new microbial habitats that can stimulate undesired microbial activities. A notable example of this is microbiologically influenced corrosion (MIC) which refers to corrosion of metallic equipment and structures caused or accelerated by microorganisms. These microorganisms are mainly bacteria and archaea, but microalgae and fungi can also be important contributors in certain environments [3, 4]. In Australia, MIC represents a common threat to the oil & gas, defence and marine industries which are major components of the national economy. Deterioration and corrosion due to microorganisms drives a worldwide market for microbial control that is worth billions of dollars annually.